2005
DOI: 10.2111/1551-5028(2005)58[324:siojcb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sire Influence on Juniper Consumption by Goats

Abstract: Goats avoid eating redberry juniper (Juniperus pinchottii Sudw.) when other palatable forages are available but will increase intake of juniper when exposed to the plant for several days. Intake of redberry juniper also differs among breeds and individual goats. Selection based on foraging habits could further improve juniper intake. The purpose of this study was to determine the influence of sires on juniper consumption. Heritability of redberry juniper intake was assessed for 3 years (1997, 1998, 2000) by pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
(21 reference statements)
3
13
1
Order By: Relevance
“…These results are similar to the results with goats; feeding juniper in individual pens increased intake over time (Bisson et al 2001;Ellis et al 2005;Dunson et al 2007). In addition, goats continue to consume juniper when released on pasture (Dietz et al 2010).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results are similar to the results with goats; feeding juniper in individual pens increased intake over time (Bisson et al 2001;Ellis et al 2005;Dunson et al 2007). In addition, goats continue to consume juniper when released on pasture (Dietz et al 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Others have speculated that goats might be adapting to the monoterpenoids in the plant (Bisson et al 2001;Ellis et al 2005). Dunson et al (2007) illustrated that goats did not adapt to juniper through changes to the rumen environment; rather, hepatic involvement seems more likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…juniper are chemically defended woody species that have invaded millions of hectares of Texas rangelands (Ansley et al 1995;Smeins et al 1997). Several studies have shown that goats will consume juniper, particularly after feeding juniper at weaning (Bisson et al 2001;Ellis et al 2005;Dunson et al 2007). Unfortunately, intake of juniper is at times limited because monoterpenoids found in the plant cause aversive postingestive feedback (Riddle et al 1996;Pritz et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…As to whether identification of HJC goats can affect population characteristics to the point of effective management of juniper at the landscape level, Ellis et al (2005) and Waldron et al (2009) estimated heritability of juniper consumption to be 11 to 13%, indicating that progress from selection has the potential to change the population, but not rapidly. The theoretical expected response to selection is given by the product of the heritability and the selection differential.…”
Section: Discussionmentioning
confidence: 99%